2014
DOI: 10.1152/physiolgenomics.00082.2014
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in the gut microbiome of constipated patients

Abstract: Previous studies using culture-based methods suggested an association between constipation and altered abundance of certain taxa of the colonic microbiome. We aim to examine the global changes in gut microbial composition of constipated patients. A cross-sectional pilot study using 16S rRNA gene pyrosequencing was performed to compare stool microbial composition of eight constipated patients and 14 nonconstipated controls. Only obese children were enrolled so that the microbiome features associated with consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
272
7
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(303 citation statements)
references
References 50 publications
15
272
7
9
Order By: Relevance
“…Decreased Prevotella abundance and, more consistently, a decreased abundance of Bifidobacteria were found in constipated subjects [65][66][67]. In our recent study, however, we did not find such associations.…”
Section: The Triangle Of Coffee Gut Motility and Microbiota -Is It contrasting
confidence: 77%
“…Decreased Prevotella abundance and, more consistently, a decreased abundance of Bifidobacteria were found in constipated subjects [65][66][67]. In our recent study, however, we did not find such associations.…”
Section: The Triangle Of Coffee Gut Motility and Microbiota -Is It contrasting
confidence: 77%
“…3) and sequencing (data not shown). Levels of Lactobacillus were significantly reduced in adults with constipation [20] but were similar when non-constipated children were compared with constipated ones [18,19]. Here, in adult stool samples, we found little difference in Lactobacillus between the two groups.…”
Section: Discussionmentioning
confidence: 42%
“…Zoppi et al [18] used culturebased techniques and observed higher colony counts in Clostridia and Bifidobacteria in children with constipation. In a recent study with pyrosequencing, Bifidobacteria and Lactobacillus were not significantly different in the stool samples when obese children with constipation were compared with obese children without constipation [19]. In contrast, Khalif et al [20] reported low levels of Bifidobacteria and Lactobacillus in stool samples from adults with chronic constipation.…”
Section: Introductionmentioning
confidence: 92%
“…9 A cross-sectional pilot study using 16S rRNA gene pyrosequencing found that patients with constipation did not exhibit decreased levels of Lactobacillus and Bifidobacterium species, but did exhibit significantly decreased levels of Prevotella. 10 Regarding methane, the presence of methanogenic bacteria has been shown to be higher in patients with slow transit constipation compared withnon-constipated controls. 4 These alterations in gut microbiota might be either a cause of FC or a consequence of this condition.…”
Section: 8mentioning
confidence: 99%